2008
DOI: 10.1111/j.1745-6584.2007.00419.x
|View full text |Cite
|
Sign up to set email alerts
|

Three‐Dimensional Geostatistical Inversion of Flowmeter and Pumping Test Data

Abstract: We jointly invert field data of flowmeter and multiple pumping tests in fully screened wells to estimate hydraulic conductivity using a geostatistical method. We use the steady-state drawdowns of pumping tests and the discharge profiles of flowmeter tests as our data in the inference. The discharge profiles need not be converted to absolute hydraulic conductivities. Consequently, we do not need measurements of depth-averaged hydraulic conductivity at well locations. The flowmeter profiles contain information a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
68
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 80 publications
(70 citation statements)
references
References 30 publications
2
68
0
Order By: Relevance
“…This is because the uncertainty and sparseness of the EBF data obscures additional information of the increasing number of injection tests in the 3-D spatial inference. These findings are consistent with Li et al (2008), who also found that the 3-D characterization of the aquifer was limited by the EBF data density. Figure 10 shows the 3-D mean field, based on the 5000 parameter sets generated from the distribution p(β,η 2 ,λ h ,λ v ,ν 2 ,u|k,z).…”
Section: Ifrc Data Analysissupporting
confidence: 81%
See 1 more Smart Citation
“…This is because the uncertainty and sparseness of the EBF data obscures additional information of the increasing number of injection tests in the 3-D spatial inference. These findings are consistent with Li et al (2008), who also found that the 3-D characterization of the aquifer was limited by the EBF data density. Figure 10 shows the 3-D mean field, based on the 5000 parameter sets generated from the distribution p(β,η 2 ,λ h ,λ v ,ν 2 ,u|k,z).…”
Section: Ifrc Data Analysissupporting
confidence: 81%
“…Compared to direct coupling of the EBF and pumping tests used in Li et al (2008), this two-step approach has a significant computational advantage. This approach is possible because we can model the flow process during the injection tests as 2-D planar flow in the horizontal plane, due to the particular site conditions as the following.…”
Section: Methodsmentioning
confidence: 99%
“…Efforts to understand the heterogeneity of aquifers have utilized down-well flowmeters (Rehfeldt et al, 1992), tracer tests (Sudicky, 1986), pumping tests (Cardiff et al, 2009;Berg and Illman, 2011), and the joint analysis of those methods (Li et al, 2008;Bohling et al, 2012). However, investigators have acknowledged that, in highly heterogeneous settings, the ability to model heterogeneity is dependent on the density and spatial distribution of the data points (Rehfeldt et al, 1992;Slater, 2007;Alexander et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The reconstructed tomograms displayed a depth integrated distribution of hydraulic conductivity and storage, and they were validated by matching the drawdown of pressure response curves that were not used for the inversion. Li et al [2008] also employed a geostatistical approach to jointly invert data from steady state pumping tests and flowmeter measurements to estimate hydraulic conductivity in three dimensions. The pumping tests were performed in 29 fully screened wells and it took about 2 h to reach steady state conditions.…”
Section: Introductionmentioning
confidence: 99%